The Factors Affecting Tourist Visits at Owabong Waterpark in Bojongsari Sub-district of Purbalingga - Riska Eristiana Anindya Putri; Rusmusi Indranjoto (EKO-REGIONAL, 2018)
This research aimed to determine the effect of income, travel cost, distance and visitor age on the number of tourist visit to Owabong Waterpark. This research is a survey research to visitors of Owabong Waterpark using accidental sampling method. Qualitative and quantitative data was derived questionnaire based interview technique. This research used multiple linear regression analysis with double log model. The result indicated that income had a positive effect on tourist visits at Owabong Waterpark. Travel cost and distance have insignificant effect on tourist visits at Owabong Waterpark. Age had insignificant effect on tourist visits at Owabong Waterpark. The implication of this research for the management of Owabong Waterpark is to continously improve the existing facilities and infrastructures to maintain the quality of tourist attraction, always innovate various vehicles attracting the visitors, conduct promotions such as discounted ticket to reach all income groups, conduct more vigorous promotions, especially in social media to be better known by the community outside Purbalingga so that Owabong Waterpark is not only visited by local tourists, but also foreign tourists.Keywords: Income, Travel Cost, Distance, Age, Social Media.